Islam e Cristianesimo: Linee per un comune dialogo? - Giuliano, Salvatore (Alpha Omega, 2013)
The Author, in this article, considers the broad theme of dialogue with Islam, suggesting, as evidenced by the title, guidelines that could be a point of reference for interreligious dialogue: the analysis of the concept of person and the idea of God implicit in the two greatest religions in the world. In tracing the historical background of the evolution of the first line of dialogue, the author highlights how the meaning of person is defined according to the specification of christological and trinitarian dogmas. He also emphasizes the richness of the Islamic tradition that interprets personal individuality as intimately connected to the existence of the Ummah, a community of believers, with the limitations and merits that come from such an approach. The second part compares the divergent idea of God in the two monotheistic religions that brings forth a different approach to faith. In conclusion we can see the possibility for a dialogue that appraises the differences, making them not a cause for dispute but a reason for reciprocal enrichment.